Noninvasive Ventilation and Rapid Enteral Feeding Advances in Preterm Infants—2-Year Follow-Up of the STENA-Cohort - Behnke, Judith; Estreich, Vanessa; Oehmke, Frank; Neubauer, Bernd Axel; Windhorst, Anita; Ehrhardt, Harald; Justus Liebig University Giessen (My University, 2023)
The importance of nutritional supply for somatic growth and neurodevelopmental outcome in very-low-birthweight infants is an established medical strategy for reducing long-term morbidities. Our cohort study on rapid enteral feeding advances using a standardized protocol (STENA) previously demonstrated a 4-day reduction of parenteral nutrition. STENA did not impede the success of noninvasive ventilations strategies but significantly less infants required mechanical ventilation. Most importantly, STENA resulted in improved somatic growth at 36 weeks of gestation. Here, we evaluated our cohort for psychomotor outcomes and somatic growth at 2 years of age. n = 218 infants of the original cohort were followed-up (74.4%). Z-scores for weight and length did not differ but the benefits of STENA for head circumference persisted until the age of 2 years (p = 0.034). Concerning the psychomotor outcome, we neither found any statistically significant differences in the mental developmental index (MDI) (p = 0.738), norin the psychomotor developmental index (PDI) (p = 0.122). In conclusion, our data adds important insights on the topic of rapid enteral feeding advances and confirms the safety of STENA with respect to somatic growth and psychomotor outcome measures.
Keywords: enteral feeding advances; nutrition; very low birthweight infants; noninvasive ventilation; neurodevelopmental outcome; ddc:630